A Theology of Migration Based on the Actions and Teachings of Pope Francis for Migrants and Refugees - Kunnath, Joby (Asian Horizons, 2024)
Migration theology is relatively a new subject, which deals with migration from a theological perspective. This paper tries to present a migration theology based on the teachings of Pope Francis. Pope Francis, who is a great friend of the migrants, refugees, and marginalized gave a new face and direction for the Church and to the theologians to deal with migration from a theological perspective. The pope proposes a theology of migration which is rooted in the bible and the traditional teachings of the Church but at the same time gives room to understand migration from the lived experience of migrants itself. In other words he suggests a “theology in migration” or “theology in move.” For this purpose, he asks the theologians to encounter the migrants so that their theology will be deepened with the “flesh and blood stories of migrants.